Genome-wide mapping of the dominance effects based on breed ancestry for semen traits in admixed Swiss Fleckvieh bulls - Khayatzadeh, N.; Mészáros, G.; Utsunomiya, Y. T. [UNESP]; Schmitz-Hsu, F.; Seefried, F.; Schnyder, U.; Ferenčaković, M.; Garcia, J. F. [UNESP]; Curik, I.; Sölkner, J. (American Dairy Science Association, 2019)
Heterosis is the beneficial deviation of crossbred progeny from the average of parental lines for a particular trait. Heterosis is due to nonadditive genetic effects with dominance and epistatic components. Recent advances in genotyping technology have encouraged researchers to estimate and scan heterosis components for a range of traits in crossbred populations, applying various definitions of such components. In this study, we defined the intralocus (dominance) component of heterosis using local genetic ancestry and performed genome-wide association analysis for admixed Swiss Fleckvieh bulls and their parental populations, Red Holstein Friesian and Swiss Simmental, for semen traits. A linear mixed model for 41,824 SNP, including SNP additive genetic, breed additive, and breed dominance effects on 1,178 bulls (148 Red Holstein Friesian, 213 Swiss Simmental, and 817 Swiss Fleckvieh) with a total of 43,782 measurements was performed. In total, 19 significant regions for breed dominance were identified for volume (2 regions on Bos taurus autosome 10 and 22) and percentage of live spermatozoa (17 regions on Bos taurus autosome 3, 4, 5, 7, 13, 14, and 17), and genes associated with spermatogenesis, sperm motility, and male fertility traits were located there. No significant region for breed dominance was detected for total number of spermatozoa. The signals for breed dominance were relatively wide, most likely due to limited numbers of recombination events in a small number of generations (10–15 generations) of crossbreeding in the recent Swiss Fleckvieh composite.
Keywords: breed dominance; dominance component of heterosis; genome-wide mapping; local genetic ancestry